The Impact of Digital Marketing and Celebrity Endorsements on Consumer Purchase Intentions in the Modern Business Landscape - Fajri, Muhammad Iqbal; Yudiandri, Tri Eko; Ratnawita, Ratnawita; Rasyid, Rulyenzi; Jati, Prihatina (International Journal of Economics Development Research (IJEDR), 2025)
The purpose of this research is to test the impact of digital marketing and celebrity endorsers on consumer purchasing interest in Wardah Brand Products. This research uses a quantitative method with regression analysis. The sampling technique in this research is using purposive sampling and the number of samples in this research is 110 respondents. The data were analyzed using Multiple linear regression analysis with the help of IBM SPSS 25. The results of this research show that digital marketing and celebrity endorsers have a positive and significant effect on consumer purchasing interest in Wardah Brand Products. The results of this study can be used as a reference for further researchers who will study similar problems.